Study of association of concomitant diseases with chemotherapy tolerability in children with active tuberculosis: results of a retrospective cohort research - M. A. Romanova; A. V. Mordyk; E. A. Merko; E. S. Leont'eva (Union of pediatricians of Russia, 2016)
Background: It is known that concomitant diseases in adults with TB contribute to the development of intolerance to chemotherapy.Objective: Our aim was to examine the association of concomitant diseases in children with tuberculosis with TB treatment tolerability.Methods: Analyzing of the adverse events (AE) occurrence frequency in the background of the standard (RF Ministry of Health order № 109) treatment with anti-TB drugs in a continuous retrospective cohort research. AE were considered to be drug-induced hepatitis, gastritis, neurotoxic and allergic reactions.Results: The authors analyzed the results of treatment of 231 children with active TB at the age from 0 to 14 years, 186 (80.5%) of which had concomitant somatic diseases. On the background of anti-tuberculosis therapy in hospital, 69 (37%) children with concomitant diseases and 22 (49%) children of the comparison group (p = 0.200) had AE. Differences in the structure of AE between the groups were not found. The most common AE were drug-induced hepatitis: they occurred in 58 (25%) children. The risk of AE on the background of anti-TB therapy was lower among girls and higher during treatment with cycloserine and fluoroquinolones.Conclusion: Concomitant diseases in children with active TB are not associated with the development of AE on the background of the anti-TB drugs therapy.